An Optimal Technique in VANET Routing Using Metaheuristic Approach - Chaudhary, Pooja; Kumar, Kamal (International Journal of Computer Sciences and Engineering, 2025)
For accurate network performance analysis of routing protocols and access technology for VANET (Vehicular Ad hoc Network), realistic road map scenarios are required. This paper refers to analysis of network performance for VANET.[1,3] Simulation of routing protocols for VANET using realistic road map scenarios provides accurate results and can be useful for design and deployment of VANET applications. For VANET, speed of mobile nodes affects the routing path stability. It is important to use real world mobility models; so that the results obtained from the simulation of VANET routing protocols correctly reflect the real-world performance. In this paper, analyses the performance in terms of throughput, packet delivery ratio, packet loss and overhead. Routing protocols like OSPF are used for performance analysis. it supposed to handle high traffic rate as well as frequent interrupt in connection. It should consume less power and utilize bandwidth efficiently. At the same time, the VANET nodes must be simple, cheap, smaller in size and efficient enough to handle traffic. In VANET system Vehicles need to communicate with the other node, for that node continuously sending RTS-CTS signals. As if number of signals increases, there is high probability of collision. Collision damages data packets .so it requires retransmission, in this we use different routing protocols through which overhead can be reduced. Effect of flooding can be suppressed by eliminating or dropping certain nodes. Hence, reliability of communication can be improved. [5]